(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the didactic and mathematical foundations of employing sequential animations in GeoGebra to teach algebra and geometry to school students. Animations provide a dynamic and visual medium through which complex mathematical concepts can be communicated clearly and interactively, enhancing students’ logical reasoning and analytical thinking skills. The instructional strategy aligns with constructivist educational theory, emphasizing student-centered learning and knowledge construction through active participation. GeoGebra facilitates the progressive demonstration of algebraic expressions, geometric constructions, and functional relationships. The structured use of animations supports a gradual understanding of mathematical content and fosters creativity and deep conceptual engagement.